Antioxidant and Antibacterial Activities of Palu Local Shallot (Allium cepa var. aggregatum L.) Extracts Using Various Solvents - Lestari, Yudith Ayu; Taroreh, Mercy I. Riantiny; Dien, Henny Adeleida; Mangundap, Selvi Alfrida (Poltekkes Kemenkes Palu, 2025)
Background: The Palu local shallot contains active compounds such as flavonoids and phenolics, which function as antioxidants to neutralize free radicals and possess antibacterial properties against pathogenic microbes. This study aimed to analyze and compare the phytochemical profile, total phenolic and flavonoid contents, antioxidant activity, metal-chelating capacity, and antibacterial potential of Palu local shallot extracts obtained using different solvents. Methods A maceration extraction method was performed using n-hexane, ethyl acetate, and ethanol. Each extract underwent phytochemical screening, total phenolic and flavonoid quantification, antioxidant assessment via the DPPH method, metal-chelating evaluation, and antibacterial testing. Results: The ethanol and ethyl acetate extracts contained alkaloids, flavonoids, saponins, tannins, and triterpenoids, while the n-hexane extract contained only alkaloids and triterpenoids. The ethyl acetate extract exhibited the highest phenolic content (30.35 ± 0.90 mg GAE/g), whereas the ethanol extract contained the highest flavonoid level (30.28 ± 0.57 mg QE/g). The strongest antioxidant activity was found in the ethanol extract (IC50 = 38.33 ± 1.85 μg/mL). The highest metal chelating activity is the ethanol extract (20.23 ± 0.54%). The ethyl acetate extract demonstrated the strongest antibacterial activity, yielding a 17.43 ± 0.85 mm inhibition zone. Conclusion: Ethanol is the most effective solvent for extracting antioxidant compounds from Palu local shallots, while ethyl acetate yields the strongest antibacterial activity.